Symposium 3: Building Co-design Strategies in Higher Education Using Technology-Enhanced Learning Scenarios: Symposium Introduction - Gros, Begoña; Garcia, Iolanda (Proceedings of the International Conference on Networked Learning, 2014)
Networked learning is “learning in which information and communications is used to promote connections: between one learner and other learners, between learners and tutors; between a learning community and its learning resources.” (Goodyear et al. 2004:2). This definition of networked learning goes beyond merely denoting ‘online learning’ or ‘e-learning’, as it encompasses theoretical assumptions about learning and how to design for learning. The idea of networked learning suggests that learning is not confined to the individual mind or the individual learner, it is located in the connections and interactions between learners, teachers and resources. As such, “networked learning theory seems to encompass an understanding of learning as a social, relational phenomenon, and a view of knowledge and identity as constructed through interaction and dialogue” (Rybertm Buus, Georgsen, 2012: 44).